Sweeping it under the rug: How government parties deal with deteriorating economic conditions - de Vries, Catherine; Solaz, Hector (Sage Journals, 2019)
Party competition in advanced industrial democracies is generally characterized as a two-dimensional space consisting of an economic and non-economic dimension. This study examines (a) the extent to which parties strategically place more emphasis on one of these dimensions vis-à-vis the other, something we coin relative emphasis, and (b) the extent to which voters perceive such shifts in relative emphasis. Our specific focus here is on government parties. We expect government parties to shift emphasis away from the economic to the non-economic dimension when economic conditions deteriorate. In doing so, they aim to reduce the importance voters attach to the economy and the degree to which voters attribute responsibility for the economy to the government. By combining expert data for 232 parties with survey data for roughly 30,000 individuals in 28 European countries in 2014, our analysis shows that while government parties generally pay more attention to the economic dimension, they shift attention to the non-economic dimension when economic conditions deteriorate. In contexts where government parties have shifted attention away from the economic to the non-economic dimension, voters overall attach less importance to the economy and attribute less responsibility to the government for the state of the economy.
Keywords: party strategy; political dimensionality; political parties; public opinion; responsibility attribution; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades